EMERGENCY PROCESSES HANDLING IN URBAN AREA USING MODIFIED DIJKSTRA METHOD - Prima Wiratama; Ary Mazharuddin Shiddiqi (JUTI: Jurnal Ilmiah Teknologi Informasi, 2021)
Emergency Aid has a very vital role in saving the patient's life. The emergency process involves two stages, namely the pre-hospital and the hospital stage. Striving for the entire emergency process is to have the fastest response time. The initial part of emergency treatment (pre-hospital) is determining the shortest and fastest route to the hospital. In addition, the availability of the targeted hospital must also be considered. We modified Dijkstra's Algorithm to produce the shortest route and the fastest time by considering the availability of the targeted hospital to support the handling of the emergency process. The modification made to the Dijkstra algorithm replaces the weight of Dijkstra's distance with a quantity representing the congestion rate and distance. Besides, the event time is estimated to determine the status of the intended hospital. As a result, Dijkstra's modification method can produce a more efficient and faster route.